DESIGN AND IMPLEMENTATION OF A SUPERMARKET MANAGEMENT SYSTEM USING UML FOR STREAMLINED INVENTORY, SALES, AND CUSTOMER MANAGEMENT - Erni Wigati (Asosiasi Dosen Muda Indonesia, 2024)
The growing demands on supermarket management have necessitated the adoption of robust systems to streamline operations such as inventory control, sales tracking, and customer management. This study introduces a UML-based design for a supermarket management system that addresses the core needs of store administration through structured modules and defined workflows. The system encompasses store registration, inventory management, sales tracking, and customer engagement, further facilitating seamless product browsing, checkout, and post-sale support. Through structured modeling, the proposed system simplifies process flows, thereby enhancing the operational efficiency and user experience in a supermarket environment. This paper details the UML diagrams used, outlines the functional processes, and discusses the potential benefits of the system for modern retail management.